Regulation of T3 Availability in the Developing Brain: The Mouse Genetics Contribution - Richard, Sabine; Flamant, Frédéric (Frontiers in Endocrinology, 2018)
Alterations in maternal thyroid physiology may have deleterious consequences on the development of the fetal brain, but the underlying mechanisms remain elusive, hampering the development of appropriate therapeutic strategies. The present review sums up the contribution of genetically modified mouse models to this field. In particular, knocking out genes involved in thyroid hormone (TH) deiodination, transport, and storage has significantly improved the picture that we have of the economy of TH in the fetal brain and the underlying genetic program. These data pave the way for future studies to bridge the gap in knowledge between thyroid physiology and brain development.